Avaliação da modulação cognitiva, locomotora, neurometabólica e da lateralidade encefálica em ratos wistar com diabetes mellitus induzidos por estreptozotocina - Schneider, Stéfanie Ingrid dos Reis (2020)
Advanced stages of Diabetes Mellitus (DM) are associated to locomotor and cognitive dysfunction. Motor deficits observed are related to diabetic neuropathy involving peripheral nerves, which increases morbidity risk in diabetic patients. In addition, central nervous system (CNS) complications during diabetes progression are relatively more subtle compared to peripheral changes. To the present moment, few studies investigated the neurological effects during the early stages of diabetes onset, mainly in experimental models. Considering the above, our study evaluated the locomotor activity, short-term and spatial memory and brain glucose metabolism before and after DM induction in adult Wistar rats. The DM was induced by intraperironeal injection of 60mg/kg of streptozotocin (STZ), which leads to pancreatic beta cells disruption and consequent induction of experimental DM 48 hours after injection. Locomotor activity was evaluated through the open field (OF) test; the memory by the novel object recognition (NOR) test and brain glucose metabolism by [18F]fluorodeoxyglucose ([18F]FDG) positron emission tomography (PET). Body weight, food and water intake, urine and fecal output as well as blood glucose levels were also evaluated throughout the experiment. Behavioral analysis demonstrated in DM group compared to control animals, alterations in short-term spacial memory observed through NOR. Regarding locomotor activity, no significant alterations were observed between groups. Global analysis of brain glucose metabolism measured by 18F-FDG uptake indicated slight alterations in important areas for short-term and working memory, emotional control and locomotion. Controls animals had increased 18F-FDG uptake in the cerebellum, whereas DM animals had no alterations. DM animals had a increase was observed in the amygdala when compared to the control groups. Hippocampus uptake was not significantly altered when analyzed as whole. However, when segmenting it into dorsal and ventral hippocampus, it was possible to observe increased tracer uptake in the dorsal hippocampus. These results suggest possible intrinsic compensatory mechanisms in early stages of DM regarding cognition and brain glucose metabolism induced. Thus, in our second part of the study, the main objective was to assess the difference in the distribution patterns of glucose metabolism, according to its laterality, using 18F-FDG as a marker in brain regions. The results demonstrated that the distribution of 18F-FDG in the brain before and after the induction of DM in adult wistar rats is not homogeneous. The brain areas that showed a difference in glucose metabolism in relation to laterality between diabetics and controls were those of the auditory cortex, orbitofrontal cortex, nucleus accumbens core and hippocampus Posterior. We demonstrate with these results that the assessment of glucose metabolism analyzed globally should be replaced by analysis using the laterality of each brain region for the use of microPET in an experimental model of diabetes induced by STZ. Further studies are necessary to evaluate possible long-term alterations after DM induction in this animal model.